Comparison of responses of parents of hearing and hearing impaired children for the questionnaire 'awareness of aspects related to hearing' - Devi, Neelamegarajan; Fakruddin, Darga Baba; Nagaraju, Basaiahgari; Belpu, Navya; Raj, Brunda L.; Ravi, Jahnavi Ajeta (International Journal of Contemporary Pediatrics, 2021)
Background: Congenital hearing loss has a profound enervating impact on the child and the family's global development in many domains. If identified during the earlier years of life and apt rehabilitative measures are sought, it would aid in the child's near-normal development and optimize the educational placement. However, parental involvement in this process is crucial. The present study aimed to ‘develop, administer and compare the scores of the questionnaire on ‘Parent’s awareness on aspects related to hearing’ among the parents of children with normal hearing and hearing impairment. Methods: A total of eighty participants, divided into group I (parents of normal hearing children) and group II (parents of children with hearing impairment), participated in the study. Results: Mann-Whitney test showed that there was a significant difference between the groups for all the subsections. The receiver operating characteristic curve was analyzed, and the cut-off scores of 26.5 were obtained. The sensitivity of 0.825 and 1-specificity of 0.225 was achieved. Conclusions: More awareness to be created among the parents of normal-hearing children not only on the risk factors of hearing loss but also on the educational options which would hoist towards inclusion.